THE CONCEPT OF LINGUISTIC COMPETENCE AND ITS COMPONENTS - Ergasheva Rano (Modern American Journals, 2025)
Linguistic competence, a foundational concept in the field of theoretical and applied linguistics, refers to a speaker's unconscious knowledge of their native language and their ability to produce and understand an infinite number of sentences, including those never heard before. First introduced by Noam Chomsky in the 1960s, the term has evolved significantly, incorporating broader aspects of language use and comprehension. This article explores the concept of linguistic competence, traces its theoretical development, and examines its core components: phonological, morphological, syntactic, semantic, and pragmatic competence. Furthermore, the article discusses the importance of linguistic competence in language learning, its role in communication, and its relevance in educational settings.
Keywords: Linguistic competence, language acquisition, syntax, phonology, morphology, semantics, pragmatics, Chomsky, language theory.